Efficacy and safety of dapagliflozin or dapagliflozin plus saxagliptin versus glimepiride as add‐on to metformin in patients with type 2 diabetes. Issue 11 (16th July 2018) - Müller‐Wieland, Dirk; Kellerer, Monika; Cypryk, Katarzyna; Skripova, Dasa; Rohwedder, Katja; Johnsson, Eva; Garcia‐Sanchez, Ricardo; Kurlyandskaya, Raisa; Sjöström, C. David; Jacob, Stephan; Seufert, Jochen; Dronamraju, Nalina; et al.
Abstract : Objective: To compare the efficacy and safety of dapagliflozin and dapagliflozin plus saxagliptin vs glimepiride as add‐on to metformin in patients with type 2 diabetes. Research design and methods: This 52‐week, multicentre, double‐blind, active‐controlled study (NCT02471404) randomized (1:1:1) patients ( n = 939; HbA1c 7.5%‐10.5%) on metformin monotherapy (≥1500 mg/day) to add‐on dapagliflozin 10 mg, dapagliflozin 10 mg plus saxagliptin 5 mg, or glimepiride 1 to 6 mg (titrated). The primary efficacy end point was change in HbA1c from baseline to Week 52. Results: Baseline mean age, diabetes duration and HbA1c were 58.4 years, 7.0 years and 8.3%, respectively. Adjusted mean HbA1c change from baseline was −1.20% with dapagliflozin plus saxagliptin and −0.82% with dapagliflozin, vs −0.99% with glimepiride (mean dose at Week 52, 4.6 mg). Changes in body weight (−3.2 kg and −3.5 kg vs +1.8 kg) and systolic blood pressure (SBP; −6.4 mm Hg and −5.6 mm Hg vs −1.6 mm Hg) were significantly greater with dapagliflozin plus saxagliptin and dapagliflozin than with glimepiride. FPG decreased significantly with dapagliflozin plus saxagliptin compared with glimepiride (−2.1 mmol/L vs −1.5 mmol/L) and was similar with dapagliflozin (−1.6 mmol/L) compared with glimepiride. Confirmed incidence of hypoglycaemia was lower with dapagliflozin regimens than with glimepiride (0 and 1 vs 13 patients) and fewer patients required rescue. Genital infections were more frequent with dapagliflozin; other AE profiles were similar. Conclusions: Dapagliflozin, saxagliptin and metformin improved glycaemic control compared with glimepiride plus metformin; add‐on of dapagliflozin alone showed efficacy similar to that of glimepiride. Both dapagliflozin regimens decreased body weight and SBP, with a lower incidence of hypoglycaemia compared with glimepiride.